Microcomputed tomography and genetic analysis of a rare case of Caffey's disease in a 5–7‐month‐old girl. (17th July 2019) - Lombardo, Daniela; Modi, Alessandra; Vergata, Chiara; Caramelli, David; Pascart, Tristan; Bertrand, Benoit; Vetro, Annalisa; Lari, Martina; Colard, Thomas
Abstract: Ancient human remains provided precious information about the health and disease of individuals from the past. Usually, diagnosis and assessment of the paleopathological remains were performed using RX analysis, tomography, and histology. However, thanks to the progress in ancient DNA recovery and sequencing, genetic information can used to support the diagnoses performed using classical approach. Here, we described the paleopathological remains of a 5 to 7‐month infant, excavated from Saint‐Jacques church (Douai, France), dated from 16th to 18th century. The skeleton displayed bone lesions, consisting in a massive corticoperiosteal thickening with subperiosteal new bone formation. To investigate the pathological condition of the remains, we applied a combined approach using both microcomputed tomography and paleogenetic analysis. Among several pathologies, we proposed a potential diagnosis of Caffey's disease (Infantile Cortical Hyperostosis, ICH), a rare genetic infantile pathology that causes a massive subperiosteal new bone formation in some diagnostic skeletal districts. Association of the disease with the COL1A1 gene on chromosome 17q21 has been highlighted in several familial cases, whereas other evidences suggest genetic heterogeneity of ICH. Although the osteological clinical picture was compatible with Caffey's disease, we did not find evidence of the mutated allele in COL1A1 gene, suggesting a diagnosis of ICH caused by a different genetic mutation. Our study represents one of the first documented historical case of Caffey's disease and highlights the contribution of paleopathological studies for a better knowledge of human diseases.